Consuming Places - Urry, John (USA; Routledge, 1995)
Urry begins with an extensive review of the connections between society, time and space. The concept of 'society', the nature of 'locality', the significance of 'economic restructuring', and the concept of the 'rural', are examined in relationship to place. The book then considers how places have been transformed by the development of service occupations and industries. Concepts of the service class and post-industrialism are theoretically and empirically discussed.
English
Keywords: Consumer practices; HC10-1085 Social Sciences- Economic history and conditions; Tourism industry